Fiscal anchors and sustainable fiscal policy - Krige Siebrits; Estian Calitz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper discusses the rationale and options for a fiscal anchor for South Africa and its potential for restoring and maintaining fiscal sustainability. It argues that a well designed fiscal anchor can be useful in the current fiscal milieu, but notes that the popularity of fiscal rules belies an uneven record and doubts about their efficacy. In view of this, the paper warns against unrealistic expectations about the impact that rules-based fiscal policy-making might have and points out that a strengthened regime of transparency-based discretion should not be disregarded as an alternative mechanism to anchor fiscal expectations in the South African context. It also emphasizes the salience of an unwavering political commitment to fiscal discipline, irrespective of the details of the fiscal policy-making framework.
Keywords: E02; E61; E63; H61; 330; fiscal anchor; fiscal rules; fiscal policy; fiscal sustainability; South Africa